2021
DOI: 10.1007/s10064-021-02441-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rockfall source areas using the seed cell concept and bivariate susceptibility modelling

Abstract: The objective of this research was to prepare a rockfall susceptibility map. Explorations were conducted in the Dubračina River basin (Croatia). The input data included a geological map, an orthophoto and a 1-m digital terrain model (DTM). After a talus inventory was prepared, the seed cell concept was applied to define the rockfall source areas. The contributing factors (predictors) of rockfalls were evaluated by the chi-squared test. The analysis confirmed the following predictors: CORINE land cover, litholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Machine learning techniques, finally, are becoming more popular given their ability to deal with large datasets and derive complex non-linear patterns [26]. In the specific case of rockfalls, research has shown rapid growth in recent years, with a clear increasing trend of annual publications on the topic, and several works based on different datasets and techniques have recently been published [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques, finally, are becoming more popular given their ability to deal with large datasets and derive complex non-linear patterns [26]. In the specific case of rockfalls, research has shown rapid growth in recent years, with a clear increasing trend of annual publications on the topic, and several works based on different datasets and techniques have recently been published [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%